Gamification and Smart Learning: A Framework for Digital Motivation - Abdulnassir Yassin; Salman Rashid; Husna Juma Mlwale (Journal of Educational Technology Innovation and Applications, 2025)
Integrating gamification techniques into smart learning environments has gained considerable attention as a method to enhance student engagement and motivation. This article explores the connection between gamification and smart learning by proposing a conceptual framework for digital motivation. Drawing upon existing literature, the paper identifies key components of gamification and smart learning and presents a model that leverages digital tools to improve educational outcomes. The results of various studies examining the effects of gamification in digital learning environments are discussed, revealing both the potential benefits and challenges of incorporating game elements into education. This paper provides valuable recommendations for educators and institutions aiming to increase student engagement and success by offering insights into how gamification can be strategically utilised within smart learning systems.